2011
DOI: 10.1161/circulationaha.110.960260
|View full text |Cite
|
Sign up to set email alerts
|

Listing and Transplanting Adults With Congenital Heart Disease

Abstract: Background-An increasing number of patients with congenital heart disease (CHD) are reaching adulthood and may require heart transplantation. The survival of these patients after listing and transplantation has not been evaluated. Methods and Results-A total of 41 849 patients (aged Ͼ18 years) were listed for primary transplantation during [1995][1996][1997][1998][1999][2000][2001][2002][2003][2004][2005][2006][2007][2008][2009]. Patients with a history of CHD (nϭ1035; 2.5%) were compared with those with other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
128
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 165 publications
(130 citation statements)
references
References 31 publications
2
128
0
Order By: Relevance
“…Early complications, relating to transplant complexity, contribute substantially to the mortality of both adults and children and have been reported across the literature (24,28,38). Survivors have comparable outcomes to all CHD recipients.…”
Section: Mortality In Sv Heart Transplantationmentioning
confidence: 99%
“…Early complications, relating to transplant complexity, contribute substantially to the mortality of both adults and children and have been reported across the literature (24,28,38). Survivors have comparable outcomes to all CHD recipients.…”
Section: Mortality In Sv Heart Transplantationmentioning
confidence: 99%
“…Davies, et al identified 1 035 adult patients with CHD who were listed for primary cardiac transplantation (2.5% of the total number). (78) They found that patients with CHD were on the waiting list for a longer time and, again demonstrated a higher early mortality in those with CHD (18.9% vs 9.6%) but an equivalent 10 year mortality (52.8% vs 53.6%). Similar results were also found by Patel, et al who further reported that patients with CHD who underwent transplantation had significantly longer intraoperative ischaemic times.…”
Section: Cardiac Transplantation In Achdmentioning
confidence: 94%
“…Two larger studies from the US examined all transplants recorded in a nationwide registry and database. (74,78) However, unlike Irving, et al, the type of CHD was not recorded. Davies, et al identified 1 035 adult patients with CHD who were listed for primary cardiac transplantation (2.5% of the total number).…”
Section: Cardiac Transplantation In Achdmentioning
confidence: 95%
See 2 more Smart Citations